1976
DOI: 10.1159/000193744
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for the Determination of the Thread-Forming Property of Tracheobronchial Secretions

Abstract: A method is described for determining the thread-forming property (‘Spinn-barkeit’) of tracheobronchial secretions. With this method it was observed that adrenergic compounds increase the length of the mucus threads by an average of 154% whereas mucolytic agents caused an average decrease of 63 % in the length of the mucus threads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Several hu man studies showed that ambroxol affects the secretomotor activity of serous glands [13,14], facilitates the repair of bronchial epithelium [15], and accelerates mucocil iary transport (in vitro model using frog palate) [16] and clearance [99mTc-labeIed secretions; ref. 17], However, as no effect was demonstrated on the viscoelasticity of bronchial secretion, ambroxol is not a true mucolytic agent [18). The aim of this trial was to determine, as previous ly investigated, the clinical efficacy of ambroxol in the treatment of bronchial stasis and also includes the following studies: study A using a daily dose of 120 mg which was considered an effective dose and study B, using a daily dose of 30 mg to determine an effective minimum dose.…”
Section: Introductionmentioning
confidence: 99%
“…Several hu man studies showed that ambroxol affects the secretomotor activity of serous glands [13,14], facilitates the repair of bronchial epithelium [15], and accelerates mucocil iary transport (in vitro model using frog palate) [16] and clearance [99mTc-labeIed secretions; ref. 17], However, as no effect was demonstrated on the viscoelasticity of bronchial secretion, ambroxol is not a true mucolytic agent [18). The aim of this trial was to determine, as previous ly investigated, the clinical efficacy of ambroxol in the treatment of bronchial stasis and also includes the following studies: study A using a daily dose of 120 mg which was considered an effective dose and study B, using a daily dose of 30 mg to determine an effective minimum dose.…”
Section: Introductionmentioning
confidence: 99%
“…It is not conclusive to explain increased transport rates of up to 300%, compared to the control rates, by a 10% stimulation Guinea pig tracheal ciliated cells 1-100 qmol/l increase in beat frequency up to 11 % this study in vitro of the ciliary activity; therefore, we need a better explanation: Iravani and Melville [2] showed that the spinability of rat air way mucus, a measure of consistency, was decreased by 62% after incubation of the excised airways in 12 /xmol/l of ambroxol. Usually, there is a correlation between changes in spinability and in the elasticity of mucus.…”
Section: Discussion and Reviewmentioning
confidence: 86%